1991
DOI: 10.1126/science.253.5016.173
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Nanometer- to Atomic-Scale Manipulation of Silicon Surfaces with the STM

Abstract: The controlled manipulation of silicon at the nanometer scale will facilitate the fabrication of new types of electronic devices. The scanning tunneling microscope (STM) can be used to manipulate strongly bound silicon atoms or clusters at room temperature. Specifically, by using a combination of electrostatic and chemical forces, surface atoms can be removed and deposited on the STM tip. The tip can then move to a predetermined surface site, and the atom or cluster can be redeposited. The magnitude of such fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
221
2
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 587 publications
(234 citation statements)
references
References 18 publications
6
221
2
2
Order By: Relevance
“…The discovery of probe-based oxidation 41 was shadowed by the more exciting experiments reporting either modifications 62 or manipulations 63 of surfaces with atomicscale capabilities 64 . However, the generality and robustness of the underlying chemical process (anodic oxidation) has transformed Dagata's observation into a reliable a versatile nanolithography approach for patterning and device fabrication 42 .…”
Section: Oxidation Splmentioning
confidence: 99%
“…The discovery of probe-based oxidation 41 was shadowed by the more exciting experiments reporting either modifications 62 or manipulations 63 of surfaces with atomicscale capabilities 64 . However, the generality and robustness of the underlying chemical process (anodic oxidation) has transformed Dagata's observation into a reliable a versatile nanolithography approach for patterning and device fabrication 42 .…”
Section: Oxidation Splmentioning
confidence: 99%
“…Recently, the scanning probe technique has emerged as a promising tool to manipulate atoms on semiconductor surfaces [1][2][3][4]. It was indeed demonstrated that H atoms on the H-covered Si(001) surfaces are removed along a Si dimer row in a controlled way [2 -4], exposing a dangling bond (DB) array on the surfaces.…”
mentioning
confidence: 99%
“…Individual large molecules can be positioned on surfaces 2±4 , and atoms can be transferred controllably between the sample and probe tip 5,6 . The most complex structures 7±11 are produced at cryogenic temperatures by sliding atoms across a surface to chosen sites.…”
mentioning
confidence: 99%